2022
DOI: 10.3389/fcimb.2021.773496
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Upper and Lower Airway Microbiotas in Paediatric Bronchiectasis Exacerbations: A Pilot Study

Abstract: IntroductionNon-cystic fibrosis bronchiectasis is a respiratory health condition with many possible aetiologies, some of which are potentially reversible in childhood with early diagnosis and appropriate treatment. It is important to understand factors which contribute to progression or potential resolution of bronchiectasis. It is evident that respiratory exacerbations are a key feature of bronchiectasis disease progression. In this pilot study we document how the microbiota of the upper and lower airways pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Despite this variability, a small number of genera are consistently observed to be among the most abundant taxa in the airway bacteriome of children with PBB or bronchiectasis, specifically: Haemophilus , Moraxella , Streptococci , and Neisseria [ 28 , 29 , 30 , 31 , 32 , 33 ]. Anaerobic taxa (e.g., Prevotella , Fusobacterium , and Veillonella ) are also common, but with higher variability in relative abundance across studies [ 28 , 29 , 31 ].…”
Section: The Lower Airway Microbiome Among Children With Pbb or Bronc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this variability, a small number of genera are consistently observed to be among the most abundant taxa in the airway bacteriome of children with PBB or bronchiectasis, specifically: Haemophilus , Moraxella , Streptococci , and Neisseria [ 28 , 29 , 30 , 31 , 32 , 33 ]. Anaerobic taxa (e.g., Prevotella , Fusobacterium , and Veillonella ) are also common, but with higher variability in relative abundance across studies [ 28 , 29 , 31 ].…”
Section: The Lower Airway Microbiome Among Children With Pbb or Bronc...mentioning
confidence: 99%
“…To date, only one study has assessed the lower airway bacteriome among children with bronchiectasis longitudinally. Broderick and colleagues [ 33 ] examined the sputum bacteriome among 30 children with bronchiectasis (median age 6 years; range 1–15 years) before and after antibiotic treatment for an acute exacerbation. Despite heterogeneity in the types of antibiotics used, no significant differences in alpha or beta diversity were observed, suggesting stability of the sputum bacteriome during treatment.…”
Section: The Lower Airway Microbiome Among Children With Pbb or Bronc...mentioning
confidence: 99%
“…In chronic respiratory tract diseases, such as bronchiectasis (BE), the microbial factor and dysfunctional immunity contribute to the pathophysiology, while the underlying cause of the disease is still unclear in a large part of cases [16]. While the lower respiratory tract microbiota of BE patients has been explored to some extent [17][18][19][20][21], the content and role of nasal microbiota in BE patients is still sparse [22]. However, in similar morbidities, like chronic obstructive pulmonary disease, lung microbiota closely reflected the oral, and nasal microbiota [23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that disturbance of the microbiome is closely related to the exacerbation of many respiratory diseases, such as bronchiectasis, asthma, COVID-19, and ventilator-associated pneumonia (4)(5)(6)(7). The pulmonary microbiome is correlated with some outcomes of MPP, such as bronchial mucus plugs and refractory MPP (8,9).…”
Section: Introductionmentioning
confidence: 99%